Pelatihan Penyusunan Laporan Keuangan Berbasis Digital Pada Usaha Penjahit Minang Baru - Soleh, Ahmad; Amabell, Selly; Agustin, Ayu; Sachanovrissa, Silke; Rahman, Abdul (Jurnal Dehasen Mengabdi, 2022)
The preparation of financial statements is one of the most important things for a business, especially the MSME business sector. However, there are still many MSME business actors who have not been able to make financial statements properly and correctly, including this New Minang Tailor business which still uses makeshift financial statements and still uses financial reports manually, thus making it difficult for the owner of this New Minang Tailor to see income. and monthly expenses. Based on the existing problems, we aim to help the owner of this New Minang Tailor business, by providing training on the preparation of Digital-Based Financial Reports (Book Warung Application), the Digital Book Warung Application is one of the digital- based financial reporting applications where it is easy and simple to use by MSME actors. The methods used in this training are: Identification, Preparation, Implementation, and Evaluation. Based on the results of this digital-based Financial Report preparation training, I got positive results in understanding and being able to apply it in this New Minang Tailor business.